Suhrawardi's Philosophical Thoughts - Maspuroh; Irma Alawiyah; Tita Peronika; Faiz Arrasyid Ahmad; Wafi Nurafiah (Bibliotheca: Journal of Philosophy, 2025)
Syihāb al-Dīn Yahyā bin Habasy bin Amīrak al-Suhrawardī (Sohrevardi), was one of the leading figures in philosophy. Suhrawardi was also known as Shaykh al- Isyrāq (Master of Illumination). The term al-Isyraq itself is a description of his isyrāqiyyah philosophical view of thought, which is a rival to peripatetic philosophy (masyāˈīyyah). Another nickname for Suhrawardi was al-Maqtūl (The Assassinated). This title is based on the fact that his death was ordered by the leader of the city of Aleppo (Halab), al-Mālik al-Zhāhir Ghiyāts al-Din Ghazī.